Legal and economic aspects of monetary regulation of the European system of central banks - Туляков, Вячеслав Олексійович; Туляков, В. О.; Туляков, Вячеслав Алексеевич; Tuliakov, Viacheslav O.; Tulyakov, Vyacheslav A.; Алексеєвська, Галина Сергіївна; Алексеєвська, Г. С.; Алексеевская, Галина Сергеевна; Alekseievska, Halyna S.; Якубовський, Сергій Олексійович; Якубовський, С. О.; Якубовский, Сергей Алексеевич; et al. (University of Zagreb, 2021)
Monetary regulation is one of the most important components of government policy. The monetary regulation policy of the European Central Bank has undergone important transformations over the past ten years as a result of measures that were taken in response to the global financial crisis of 2008. Today the main problem of the ECB is not inflation, but stimulation of the post-crisis development of European countries. As a result, many new elements have been added to the ideology and practice of monetary regulation. Moreover, new challenges, such as a pandemic, are prompting the ECB to seek new means of influencing financial markets and, ultimately, the real sector of the economy. The paper presents the modern system of monetary regulation in the EU, characterizes its structure and legal status. The consequences of the application of unconventional measures of monetary regulation in the EU in the period after the 2008 crisis and during the COVID 19 crisis were determined. The effectiveness of the ECB’s actions in overcoming the crisis was analyzed. On the example of the decision of the Federal Constitutional Court of Germany, the reasons were identified and the consequences of the conflict between the EU legislation and national legislation in the issue of the jurisdiction of monetary regulation were assessed.

Грошово-кредитне регулювання є однією з найважливіших складових державної політики. Політика грошово-кредитного регулювання Європейського центрального банку за останні десять років зазнала важливих трансформацій у результаті заходів, які були вжиті у відповідь на світову фінансову кризу 2008 року. Сьогодні головною проблемою ЄЦБ є не інфляція, а стимулювання посткризового розвитку європейських країн. У результаті до ідеології та практики грошово-кредитного регулювання було додано багато нових елементів. Більше того, нові виклики, такі як пандемія, спонукають ЄЦБ шукати нові засоби впливу на фінансові ринки і, зрештою, на реальний сектор економіки. У роботі представлено сучасну систему монетарного регулювання в ЄС, охарактеризовано її структуру та правовий статус. Визначено наслідки застосування нетрадиційних заходів монетарного регулювання в ЄС у період після кризи 2008 року та під час кризи COVID-19. Проаналізовано ефективність дій ЄЦБ щодо подолання кризи. На прикладі рішення Федерального конституційного суду Німеччини виявлено причини та оцінено наслідки колізії між законодавством ЄС та національним законодавством у питанні юрисдикції грошово-кредитного регулювання.
Tuliakov V. Legal and economic aspects of monetary regulation of the European system of central banks / V. Tuliakov, H. Alekseievska, S. Yakubovsky // InterEULawEast. - Vol. 8(2). - University of Zagreb, 2021. - P. 79-96.
Keywords: monetary regulation; legal regulations; unconventional instruments; COVID 19 pandemic; contradictions between EU law and national legislation; грошово-кредитне регулювання; правове регулювання; нетрадиційні інструменти; пандемія COVID-19; суперечності між законодавством ЄС та національним законодавством; Research Subject Categories::LAW/JURISPRUDENCE